Laparoscopic versus open surgical management of idiopathic varicocele: a study on 100 patients - Verma, Deepak; Lal, Chhanwar; Sharma, Avdhesh; Sirwi, Manoj (International Surgery Journal, 2017)
Background: Idiopathic varicocele is common condition encountered in surgical practice requiring surgical correction. Open surgical technique had been in use for long but laparoscopic varicocelectomy is another choice for its management. Methods: This is a prospective study on 100 patients. 70 patients were subjected to laparoscopic and 30 to open inguinal varicocelectomy. Results: Majority of patients were between 16 to 25 years of age. 55% were asymptomatic and 10% had infertility. Grade II varicocele was observed in 50% patients. All patients had left side involvement with bilateral varicocele in 2% patients. Mean operating was 13.8 min in unilateral and 17.3 min in bilateral laparoscopic varicocelectomy whereas it was 27.55 min in unilateral and 49.7 min in bilateral open varicocelectomy. 5.7% and 6.6% had secondary hydrocele and hospital stay was 1.25 and 3.4 days in laparoscopic and open group respectively. Conclusions: Laparoscopic varicocelectomy is safe, effective procedure with less post-operative pain and analgesic requirement. It also has shorter operating time and post-operative hospital stay. Procedures like opposite varicocele, herniotomy, adhesiolysis or orchiopexy can also be done.